1973
DOI: 10.1128/am.26.3.391-393.1973
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Three Selected Bacterial Species to Ozone

Abstract: The minimal lethal concentration of ozone in water was determined for three bacterial species: Escherichia coli, Bacillus cereus , and Bacillus megaterium . A contact period of 5 min was selected. The lethal threshold concentration for the cells of B. cereus was 0.12 mg/liter while that for E. coli and B. megaterium was 0.19 mg/liter. Low concentrations of ozone were ineffective when organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(38 citation statements)
references
References 9 publications
2
36
0
Order By: Relevance
“…Seemingly, it also shows superior results in the treatment of biofilms as compared to antibiotics. (17,19,20,21,22,23,24). Ozone therapy for infections seems to have similarities with hyperbaric oxygen treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seemingly, it also shows superior results in the treatment of biofilms as compared to antibiotics. (17,19,20,21,22,23,24). Ozone therapy for infections seems to have similarities with hyperbaric oxygen treatment.…”
Section: Discussionmentioning
confidence: 99%
“…(16) Laboratory findings indicate ozone to have a high destructive potential on vegetative and planktonic forms of bacteria immersed in water and/or saline solution. (17) Results on its activity on biofilms are not so univocal however, ozone seems to have better destruction capacity then common treatment with antibiotics (18,19,20,21,22,23,24) Toxicological tests found that ozone, as applied to laboratory animals in acute and subacute doses, didn't show any tissue damage when studied either under electronic microscopy or histology. (25) We report a case of post-operative spine surgery infection treated successfully with intra-wound application of gaseous form of ozone.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with ozone is a relatively new concept in dentistry. Ozone is a very powerful bactericide that can kill microorganisms effectively even at a concentration as low as 0.1ppm [16] . There are several known actions of ozone on human body, such as anti-microbial, immunostimulating, antihypoxic, analgesic, detoxicating, bioenergetic and biosynthetic (activation of the metabolism of carbohydrates, proteins & lipids) etc.…”
Section: Discussionmentioning
confidence: 99%
“…All the irrigation solutions at our disposable have their share of limitations and the search for an ideal root canal irrigant continues with the development of newer materials and methods [15] . Broadwater et al in 1973 reported that ozone at low concentration, 0.1 ppm, is sufficient to inactivate bacterial cells including their spores [16] . Ozone dissociates readily back into oxygen (O 2 ), thus liberating so called singlet oxygen (O 1 ), which is a strong oxidizing agent.…”
Section: Introductionmentioning
confidence: 99%
“…22 Ozone in concentration of 0.1ppm is effective for inactivating the growth of the bacteria. 23 Ozone therapy increases oxygen perfusion to the tissues by the erythrocytes due to activation of 2,3diphosphoglycerate which in turn is activated due to increase in the red blood cell glycolysis rate. Ozone also stimulates production of ATP via Krebs cycle by enhancing oxidative carboxylation of pyruvate.…”
Section: Anti-microbial Effectmentioning
confidence: 99%